Orthognathic surgery for patients with fibrous dysplasia involved with dentition - Santhiya Iswarya Vinothini Udayakumar; Jun-Young Paeng; So-Young Choi; Hong-In Shin; Sung-Tak Lee; Tae-Geon Kwon (SpringerOpen, 2018)
Abstract Background Fibrous dysplasia (FD) is characterized by the replacement of normal bone by abnormal fibro-osseous connective tissue and typically treated with surgical contouring of the dysplastic bone. When dysplastic lesions involve occlusion, not only is surgical debulking needed, orthognathic surgery for correction of dentofacial deformity is mandatory. However, the long-term stability of osteotomized, dysplastic bone segments is a major concern because of insufficient screw-to-bone engagement during surgery and the risk of FD lesion re-growth. Case presentation This case report reviewed two patients with non-syndromic FD that presented with maxillary occlusal canting and facial asymmetry. Le Fort I osteotomy with recontouring of the dysplastic zygomaticomaxillary region had been performed. The stability of osseous segments were favorable. However, dysplastic, newly formed bone covered the previous plate fixation site and mild bony expansion was observed, which did not influence the facial profile. Including the current cases, 15 cases of orthognathic surgery for FD with dentition have been reported in the literature. Conclusion The results showed that osteotomy did not appear to significantly reduce the long-term stability of the initial fixation insufficiency of the screw to the dysplastic bone. However, based on our results and those of the others, long-term follow-up and monitoring are needed, even in cases where the osteotomized segment shows stable results.